This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Convergence needs to be proved...
This is one of the Ramanujan-style infinite radicals. Consider the sequence of functions g m : [ 0 , ∞ ) → [ 0 , ∞ ) defined inductively as follows: g 0 ( c ) = c g m ( c ) = c 2 + g m − 1 ( 2 c ) c ≥ 0 , m ∈ N It is clear that g m ( c ) ≥ c for all c ≥ 0 and m ≥ 0 . Certainly g o ( c ) ≤ c for all c ≥ 0 . If g m − 1 ( c ) ≤ c + 1 for all c ≥ 0 , it follows that g m ( c ) 2 ≤ c 2 + ( 2 c + 1 ) = ( c + 1 ) 2 , so that g m ( c ) ≤ c + 1 for all c ≥ 0 . Thus we deduce by induction that c ≤ g m ( c ) ≤ c + 1 c ≥ 0 , m ≥ 0 Since 0 ≤ c + 1 − g m ( c ) = c + 1 + g m ( c ) ( c + 1 ) 2 − g m ( c ) 2 ≤ c + 1 + g m ( c ) ( c + 1 ) 2 − c 2 − g m − 1 ( 2 c ) ≤ 2 c + 1 2 c + 1 − g m − 1 ( 2 c ) for all c ≥ 0 and m ≥ 1 , we deduce by induction that 0 ≤ c + 1 − g m ( c ) ≤ ( 2 c + 1 ) ( 4 c + 1 ) . . . ( 2 k c + 1 ) 2 k c + 1 − g m − k ( 2 k c ) c ≥ 0 , 1 ≤ k ≤ m so that 0 ≤ c + 1 − g m ( c ) ≤ ( 2 c + 1 ) ( 4 c + 1 ) . . . ( 2 m c + 1 ) 2 m c + 1 − g 0 ( 2 m c ) ≤ 2 m c + 1 1 c ≥ 0 , m ≥ 0 and hence m → ∞ lim g m ( c ) = c + 1 c > 0 In this case we have c = 2 , and hence the infinite radical equals 3 .
Problem Loading...
Note Loading...
Set Loading...
3 = 4 + 5 = 4 + 1 6 + 9 = 4 + 1 6 + 8 1 = 4 + 1 6 + 6 4 + 1 7 So , 3 = 4 + 1 6 + 6 4 + 2 5 6 + 3 3 ⋯